Formulasi Kebijakan Program Banyuwangi Hijau, dalam Mewujudkan Pengelolaan Sampah Berkelanjutan (Studi di Desa Bunder, Kecamatan Kabat) - Wafa, Ali; Angin, Ria (Jurnal Pemerintahan dan Politik, 2024)
Background: The high volume of waste in Banyuwangi Regency, which reaches 1,245 tons every day, is a serious threat and needs to be addressed through alternative waste management programs. Household waste and low public awareness are major contributors to the waste pile. The Banyuwangi Regency Government through the green Banyuwangi program is expected to be the most up-to-date solution for sustainable waste management. Research Objectives: To find out how the policy formulation of the Banyuwangi green program, within the Bunder Village Government, Kabat District. Research Methods: Using qualitative methods, by conducting field survey activities and in-depth interviews with actors who play an active role in the Banyuwangi Hijau program, and program triggering documents that explain the participation of Bunder Village community. Research Results: The Banyuwangi Hijau program is a very cheap and aligned program, so that it gets high community participation, gets subsidies from the Banyuwangi Regency APBD & the proceeds from the sale of waste sorting, and the program is regulated independently in two Bunder Village Regulations compiled jointly with the Environmental Service (DLH) and the Village Consultative Body (BPD), as well as BUMDes as the body that collects fees and provides services.